2007
DOI: 10.2298/tsci0701043m
|View full text |Cite
|
Sign up to set email alerts
|

Laminar air flow free convective heat transfer inside a vertical circular pipe with different inlet configurations

Abstract: Free con vec tion heat trans fer has been ex per i men tally in ves ti gated for lami nar air flow in a ver ti cal cir cu lar pipe by us ing the bound ary con di tion of con stant wall heat flux in the ranges of lo cal Rayleight num ber (Ra L ) from 1.1·10 9 to 4.7·10 9 . The ex per i men tal setup was de signed for de ter min ing the ef fect of dif fer ent con fig u ra tions placed at the in let of a ver ti cal heated pipe, on the sur face tem per a ture, the lo cal and av er age heat trans fer co ef fi cient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…He showed that the inlet conditions and conflgurations have a tremendous effect on the heat transfer results. These same authors [6] have presented a numerical work with a computational model that has been successfully validated by comparing their experimental results [5] and other authors. Kurnia et al [7] have carried out a parametric study of laminar flow and heat transfer characteristics of coils made of tube of several different cross-sections with the aim to conduct the geometrical effect on the heat transfer performance.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…He showed that the inlet conditions and conflgurations have a tremendous effect on the heat transfer results. These same authors [6] have presented a numerical work with a computational model that has been successfully validated by comparing their experimental results [5] and other authors. Kurnia et al [7] have carried out a parametric study of laminar flow and heat transfer characteristics of coils made of tube of several different cross-sections with the aim to conduct the geometrical effect on the heat transfer performance.…”
Section: Introductionmentioning
confidence: 97%
“…It is reported that neglecting the circumferential conduction within the pipe thickness leads to an overestimation of the azimuthally wall temperature difference, at a given pipe section. Extensive experimental data was provided by Mohammed et al [5] on uniformly heated constant wall heat flux in a vertical circular pipe with different inlet conflgurations: cylindrical pipes with different length, sharp-edge, and bell-mouth. He showed that the inlet conditions and conflgurations have a tremendous effect on the heat transfer results.…”
Section: Introductionmentioning
confidence: 99%